Outcomes of COVID-19 patients with STEMI undergoing primary PCI. (3rd October 2022) - Kleczynski, P; Niewiara, L; Kulbat, A; Kaczynski, M; Pawlowski, T; Socha`, S; Rakowski, T; Gil, R; Bartus, S; Legutko, J
Abstract: Introduction and aim: Coronavirus disease (COVID-19) has substantial impact on acute myocardial infarction (AMI) clinical course and outcome. In Poland during early phase of COVID-19 pandemic a network of dedicated hospitals was set to treat SARS-Cov2 positive patients. There is scarce data on STEMI patients outcome treated in this setting. Our aim was to compare outcomes of STEMI patients treated with primary PCI in hospitals dedicated to treat COVID-19 and referral high volume haemodynamic centres. Methods: Study was a retrospective analysis of 115 consecutive COVID-19 patients with STEMI, treated with primary PCI, admitted to 4 high volume centres (2 referral hospitals and 2 COVID dedicated sites) in southern Poland between May 2020 and November 2021. Data was obtained from patients' electronic medical records. Results: Detailed characteristics are presented in Table 1 and 2. In general in all hospitals, patients were similar in terms of age (median 69 y.o., IQR: 60–73), with similar profile of comorbidities. All patients used acetylsalicylic acid and unfractioned heparin. In referral centres, as compared with COVID-19 dedicated sites, there was a higher use of mechanical thrombectomy (p<0.001) and adenosine (p<0.001). Overall mortality rate was higher in COVID-19 centres (50% vs 25%, p=0.008). Detailed results are presented in Table 3. Conclusions: There is a significantly higher mortality in COVID patients who develop STEMI than in patients with STEMI who were tested positive on admission. Patients in COVID-19 hospitals had higher levels of CRP and NT-proBNP at baseline. There are substantial differences in treatment of patients in referral centres and COVID dedicated hospitals. Funding Acknowledgement: Type of funding sources: None.